Hantzschia subandina Frenguelli (Bacillariophyceae): Morfología, status y tipificación, asi como la descripción de una nueva especie de Nitzschia - Kociolek, John P. (2020)
Background and aims: Hantzschia Grunow is a genus characterized by having valves asymmetric to the apical axis, markedly dorsiventral, with an eccentric raphe on the ventral side supported by fibulae and ‘hantzschioid’ symmetry of the frustules. In 1942 J. Frenguelli published the flora of diatoms of Neuquén province (Argentina), work in which he erected Hantzschia subandina as a new species for science. This work investigates the identity and taxonomic status of this taxon. M&M: Original material of Hantzschia subandina of the Frenguelli Collection was analysed with light and scanning electron microscopy. Results and Conclusions: Observations on the material suggested two different species were included in the concept of this species assigned originally to the genus Hantzschia. Furthermore, neither of the two species present are assignable to the genus Hantzschia. Nitzschia subandina (Frenguelli) comb. nov. has a large central nodule and a slight asymmetry about the apical axis; it also produces frustules with nitzschioid and hantzschioid symmetry. We designate a lectotype for this taxon. In addition, another diatom in the same material with slight asymmetry about the apical axis has distinctive ornamentation on the mantle of the valve and produces nitzschioid and hantzschioid frustules. For this taxon we tentatively assign it to the non-monophyletic genus Nitzschia, describing it as N. araucana sp. nov. We discuss the possible phylogenetic position of this new taxon, and suggest that the genus Nitzschia is “the next Navicula” ready to be further subdivided into distinct genera.